1980
DOI: 10.1094/pd-64-549
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of Conidia ofPeronospora tabacinaAfter Freezing and Thawing

Abstract: Conidia of Peronospora tabacina, the incitant of tobacco blue mold, attached to infected leaves or suspended in aqueous suspensions remained infective for more than 3 mo at-20 C. Conidia on sporulating lesions survived after six repeated cycles of freezing (-20 C) and thawing (25 C), whereas conidia suspended in water survived after two such cycles. Conidia on sporulating lesions stored at 5 C (100% RH) survived more than 34 but less than 57 days. The possible epidemiologic implications of this feature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The fact that oospores of Peronospora tabacina do not play an essential role in primary infection in southern Europe (CORESTA, 1961(CORESTA, , 1962 and Australia (Cruickshank, 1958(Cruickshank, , 1961(Cruickshank, , 1989 suggests that the asexual stage of the pathogen is very important in spreading the disease. Many studies (Hill, 1962;Krober, 1965;Cohen & Kuc, 1980;Cohen & Eyal, 1984;Gayed & Brow, 1984;Cruickshank, 1989) have indicated that sporangia of P . tabacina have very strong survivability and high dispersal potential, and thus take a very significant part in the epidemiology of tobacco blue mould.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that oospores of Peronospora tabacina do not play an essential role in primary infection in southern Europe (CORESTA, 1961(CORESTA, , 1962 and Australia (Cruickshank, 1958(Cruickshank, , 1961(Cruickshank, , 1989 suggests that the asexual stage of the pathogen is very important in spreading the disease. Many studies (Hill, 1962;Krober, 1965;Cohen & Kuc, 1980;Cohen & Eyal, 1984;Gayed & Brow, 1984;Cruickshank, 1989) have indicated that sporangia of P . tabacina have very strong survivability and high dispersal potential, and thus take a very significant part in the epidemiology of tobacco blue mould.…”
Section: Introductionmentioning
confidence: 99%